Differential Effect of Wortmannolone Derivatives on MDA-MB-231 Breast Cancer Cells - ACUÑA, ULYANA MUÑOZ (Anticancer Res, 2017)
BACKGROUND/AIM: The survival rate of women diagnosed with triple-negative breast-cancer (TNBC) remains low. Hence, this study aimed at the chemical and biological optimization of furanosteroid derivatives for the treatment of this type of malignancy using TNBC cells. MATERIALS AND METHODS: Semi-synthetic analogs of wortmannolone (1–6) that negatively affected the aberrant pathways in tumor cells were evaluated in hormone-independent breast cancer cells using western blot and cell cycle analysis. RESULTS: Wortmannolone derivatization generated NF-κB inhibitors as new lead structures for further development. Compound (3) was found to be the most significantly active lead. CONCLUSION: Structure-activity analysis in the present study showed that acetylation of the hydroxyl groups and substitution on C3 and C17 of wortmannolone enhanced biological activity. Alpha-substitution of the acetyl group in C3 on ring A (compound 3) resulted in ROS inducing effect; however, presence of an acetyl group in β-position of C3 displayed the highest NF-κB p65 inhibitory activity (0.60 μM).